Analisis Pengaruh Konflik Peran Ganda dan Stres Kerja terhadap Kinerja Karyawan Wanita Menikah (Studi pada PT. Sukorintex Batang) - Rokhayatul Karomah (Universitas Wahid Hasyim, 2019)
Abstract Multiple conflict is a situation where is a sonflict betwen work assigments and tasks in the family that both demand priority. While work stress is a feeling that ia pressing or feeling depressed experienced by employees in the face of their work. This study aims to analyze the influence of multiple role conflict and work stress on the performance of married female employees at PT. Sukorintex Batang. In this study the data used are primary data and secondary data. The population in this study were married female employees in thedivision Packaging, amounting to 128 respondents. While the method used in sampling is probability sampling, which consists of sensor parts and cutter parts with a total of 90 respondents. The results of the t test (partial) in this study show that t count 9.259> t table 1.98 or p